Marketing experiencial y la satisfacción de los clientes en restaurantes de hoteles cinco estrellas de Manta - Castillo Palma, Ginger Nallely (2025)
In recent years, experiential marketing has gained importance as a key strategy to enhance service perception in highly competitive sectors such as hospitality. Within this context, the present research aimed to evaluate experiential marketing and its influence on customer satisfaction in five-star hotel restaurants in Manta city. The study followed a mixed-methods approach, combining qualitative and quantitative methods for a comprehensive understanding of the phenomenon. A descriptive methodology and a correlational method were applied to identify the strength and direction of the relationship between the variables. The survey technique was used with an ad hoc scale designed based on validated scales. Results showed a significant correlation between experiential marketing and service quality, with a Spearman coefficient of 0.869, highlighting the sensory and cognitive dimensions as the most influential on customer satisfaction. Additionally, responsiveness and emotional connection were identified as the most critical factors in the consumer experience. In conclusion, experiential marketing positively impacts perceived quality and customer loyalty, making its strategic application in the hotel sector an effective way to create memorable and distinctive experiences.